2020
DOI: 10.1177/1049732320971235
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Experiences of Women With Polycystic Ovary Syndrome (PCOS) in Ontario, Canada

Abstract: Polycystic ovary syndrome (PCOS) is the most common endocrine syndrome that disproportionally affects women of childbearing age (~8% to 13% of women worldwide). If unmanaged, it can lead to chronic, lifelong complications. Over the past decade, improvements in diagnostic guidelines have not produced an expected reduction in the diagnostic timeframe. We examined the potential reasons underlying this diagnosis delay. Participants first constructed a diagnostic timeline and then charted and reflected on their dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 46 publications
2
22
0
Order By: Relevance
“…Several guidelines have been published in the last 5–10 years detailing the need for mental health screening at the time of diagnosis [ 13 , 15 , 17 ]. Although previous studies and guidelines had been published to highlight the importance of mental health screening with PCOS, recent data from this study and others [ 28 30 ] suggests that so far that clinical shift does not appear to have occurred yet.…”
Section: Discussionmentioning
confidence: 59%
“…Several guidelines have been published in the last 5–10 years detailing the need for mental health screening at the time of diagnosis [ 13 , 15 , 17 ]. Although previous studies and guidelines had been published to highlight the importance of mental health screening with PCOS, recent data from this study and others [ 28 30 ] suggests that so far that clinical shift does not appear to have occurred yet.…”
Section: Discussionmentioning
confidence: 59%
“…Therefore, we leveraged this directed access to improve the quality of care for our study cohort. Accordingly, caution should be exercised in future research to promote this approach, since we and others have shown PCOS is often difficult to diagnose and poorly understood by healthcare providers [32,61], thus highlighting the need to establish an accurate diagnosis and provide evidence-based care to this clinical population.…”
Section: Discussionmentioning
confidence: 99%
“…Despite notable exceptions (e.g., Kitzinger & Willmott, 2002;Soucie et al, 2021a), scholars have not attempted to deconstruct what is considered "normal" regarding societal expectations of normative femininity for (young) women with PCOS. Young women have to balance gendered power dynamics, such as the physician-patient relationship (Nimmon & Stenfors-Hayes, 2016).…”
Section: The Unique and Underrepresented Experiences Of Young Women With Pcosmentioning
confidence: 99%
“…Since women occupy various social locations, knowing the ways these identities and power differentials intersect to create systems of oppression is important, and has been echoed in feminist urgings to engage in intersectional analyses (e.g., Purdie-Vaughns & Eibach, 2008). It may also be challenging because young women feel they are directly contradicting societal expectations through their experiences (e.g., Soucie et al, 2021a). Balancing gendered expectations and power differentials is a reality for young women with PCOS and a critical feminist inquiry is essential, especially as a way to consider the unique combination of identity-related aspects to experience.…”
Section: The Unique and Underrepresented Experiences Of Young Women With Pcosmentioning
confidence: 99%
See 1 more Smart Citation